Students' Perception toward Morning Vocabulary Activity - Rachmawati, Rossa Medina; Ramadhani, Syafitri (Universitas Negeri Padang, 2024)
The objective of this research was to find out students’ perception toward morning vocabulary activity at SMP Nurul Ikhlas Padang Panjang. This research used descriptive quantitative methods with questionnaire and interview to obtain the data. Both instruments are divided into three aspects; cognitive, affective and conative that related to students’ perception toward morning vocabulary activity. The sample in this research were 67 students of grade VIII at SMP Nurul Ikhlas Padang Panjang. The researcher used descriptive statistical analysis in SPSS and Miles and Hubermans’s data Theory to analyzed the data from the instrument. Based on the findings from the questionnaire, shows that most of students gave strongly positive perception with the total average was 3,46. These results were strengthened by the results of interview data that almost all students stated that morning vocabulary activity was able to increase students' vocabulary and improve several students' skills in English, which are speaking, listening and reading.